Telemedicine in Low- and Middle-Income Countries During the COVID-19 Pandemic: A Scoping Review - Mahmoud, Kareem; Jaramillo, Catalina; Barteit, Sandra (Frontiers in Public Health, 2022)
Background: COVID-19 has impacted the capacity of healthcare systems worldwide, particularly in low- and middle-income countries (LMICs), which are already under strain due to population growth and insufficient resources. Since the COVID-19 pandemic’s emergence, there has been an urgent need for a rapid and adequate reaction to the pandemic’s disruption of healthcare systems. To this end, telemedicine has been shown in prior research to be a feasible approach. The overarching objective of this scoping review was to determine the extent and acceptance of telemedicine in healthcare in low- and middle-income countries (LMICs) during the COVID-19 pandemic. Methods: This scoping review followed PRISMA guidelines and Arksey and O’Malley’s five-stage framework to identify available evidence. We systematically searched four academic databases for peer-reviewed literature published between January 2020 and April 2021: Medline, PubMed, Web of Science, and Scopus, as well as Google Scholar as a source for grey literature. Results: The search identified 54 articles with 45,843 participants, including 6,966 healthcare professionals and 36,877 healthcare users. We identified a range of reasons for introducing telemedicine in LMICs during COVID-19, most notably to maintain non-emergency healthcare, enhance access to healthcare providers, and reduce the risk of infection among health users and providers. Overall, healthcare providers and users have shown a high level of acceptance for telemedicine services. During the COVID-19 pandemic, telemedicine provided access to healthcare in the majority of included articles. Nonetheless, some challenges to accepting telemedicine as a method of healthcare delivery have been reported, including technological, regulatory, and economical challenges. Conclusion: Telemedicine was found to improve access to high-quality healthcare and decrease infection risk in LMICs during COVID-19. In general, infrastructure and regulatory barriers found to be the most significant barriers to wider telemedicine use, and should be considered when implementing telemedicine more broadly. There appears to be a need to prioritize patient data safety, as many healthcare practitioners utilized commercial apps and services as telemedicine systems. Additionally, it appears as though there is a need to increase capacity, skill, and transparency, as well as to educate patients about telemedicine.